Souvenirs and Souvenir Marketing: A new Approach Towards Creating Remembrance and Mementoes for Bangladesh as a Tourism Destination - Jahan, Nusrat; Fariha, Mahfuza Sultana (Dhaka University Journal of Business Studies, 2021)
Besides tourists’ rational causes, emotional attachments with a destination are vital for creating memories. Uniquely representing a country via memorabilia such as souvenirs could be an exciting way to extend the tourist experience and create a competitive advantage. However, souvenirs’ significance in destination image and creating memory has been ignored previously by tourism scholars of Bangladesh. This study examined souvenirs as a form of memorabilia enhancing tourists’ attachment with destination and re-visit intentions. Therefore, this paper analyzes Bangladesh’s souvenir market’s current scenario with qualitative research design by applying the case study and in-depth interview method. The findings portray advancement in the marketing of souvenirs plays an essential role in creating tourists’ memories. Hence, tourism stakeholders could use souvenir marketing as a new tool to rebrand Bangladesh as a destination. Journal of Business Studies, Vol. XLII, No. 1, April 2021 Page 87-105